The effect of age and sex on pelvic bone density measured opportunistically in clinical CT scans. Issue 3 (13th July 2020) - Telfer, Scott; Brunnquell, Christina L.; Allen, Jerad D.; Linnau, Ken F.; Zamora, David; Kleweno, Conor P.
Abstract: Unstable pelvic ring fractures are severe and complex injuries, and surgical fixation is challenging and can be complicated by early failure due in part to difficulties with securely fixing screws in low‐density bone. There is limited information in the literature about how the density distribution across the pelvic bones changes with age and sex. In this study, we used 60 sets of calibrated bone density measurements obtained opportunistically from clinical computed tomography scans of the pelvis. Three‐dimensional models of the innominate bone were produced and the effects of age and sex on cortical bone density modeled. Overall trends and regions where these factors had a significant effect were identified, and the results visualized. Across the entire innominate bone, the mean loss of density was found to be 1.6 mg/cc per year, with several specific areas (pubic body, iliac fossa, posterior ilium, and anterior inferior iliac spine for example) showing significant rates of loss up to three times greater than the rest of the bone. Areas significantly affected by sex included the posterior pubic root, anterior aspect of the pubic body, and iliac crest. Despite overall trends of attenuation, there remains significant variability between individuals. This supports the need to further explore subject‐specific planning tools for pelvic fracture repair. Statement of clinical significance : Bone density changes across the innominate bone due to age and sex tend to vary between individuals, although consistent effects were seen at specific regions. This information may help in surgical planning of unstable fracture repairs.